Inovasi Kebijakan Publik Melalui Aplikasi Terintegrasi - Muhammad Rachmadani Tarmiji; Lilis Hariyana; Riko Ajie Prabowo; Uni W Sagena (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze the implementation of public policies through integrated applications, with a case study on the Samarinda Integrated Application (SANTER). The SANTER application is part of the Samarinda City Government's initiative to realize the smart city concept, which aims to improve the efficiency of public services, strengthen transparency, and facilitate interaction between the government and the community. This study uses Edward III's theory of public policy implementation, which includes four main elements: communication, resources, disposition, and bureaucratic structure. The analysis was conducted by collecting secondary data from annual reports, user satisfaction surveys, and news articles related to the implementation of the SANTER application. The results show that effective communication between the government, policy implementers, and the community is crucial to the success of this application. Adequate human resources and technology are also key factors, although there are still challenges in terms of limited resources at the sub-district and village levels. The disposition or attitude and commitment of public officials towards the SANTER application is very positive, as demonstrated by the full support of the mayor and heads of relevant agencies. An efficient bureaucratic structure and good coordination between agencies also played an important role in the implementation of this application.